Students' Mathematics Literacy Capability In Discovery Learning Reviewed From The Existence Of Learning Media - Ghozali, Muhammad (Program Studi Pendidikan Matematika, Universitas Pancasakti Tegal, 2023)
The aim of this research is to determine students' mathematical literacy abilities in discovery learning in terms of the presence of learning media. The method used in this research is a descriptive qualitative approach. This research was conducted at MAN Tegal, Tegal City with research subjects namely class XI Science and sampling using cluster random sampling. Data collection techniques used observation, interviews and tests. The data analysis techniques used are data reduction, data presentation and drawing conclusions and using data triangulation. The results of the research show that (1) students at the high level of mathematical literacy ability can complete all indicators and reach level 4. (2) students at the medium level of mathematical literacy ability fulfill 3 indicators and. reached level 3. (3) students in the low category of mathematical literacy ability only met 2 indicators of literacy ability and reached level 2